Harnessing microbial allies: enhancing black alder resilience to PAH stress through microbial symbiosis - Striganavičiūtė, Greta; Vaitiekūnaitė, Dorotėja; Šilanskienė, Milana; Sirgedaitė-Šėžienė, Vaida (Frontiers in Plant Science, 2025)
Polycyclic aromatic hydrocarbons (PAHs) are persistent environmental pollutants that pose significant risks to plant health and ecosystem function. Phytoremediation, using plants in combination with microorganisms, offers a promising strategy for mitigating PAH toxicity. This study investigates the role of PAH-degrading microorganisms in mitigating the phytotoxic effects of PAHs on black alder (Alnus glutinosa L.) seedlings. Specifically, we examined the effects of three microbial strains—Pseudomonas putida Trevisan, Sphingobium yanoikuyae Yabuuchi et al., and Rhodotorula sphaerocarpa (S.Y. Newell & Fell) Q.M. Wang, F.Y. Bai, M. Groenewald & Boekhout—on plant growth and biochemical responses under exposure to naphthalene, pyrene, phenanthrene, and fluorene. The results revealed genotype-dependent variations in plant responses. In family 13-99-1K, S. yanoikuyae significantly enhanced defense mechanisms under phenanthrene exposure, evidenced by reduced malondialdehyde (MDA) levels and increased antioxidant enzyme activity. In contrast, family 41-65-7K exhibited stable shoot height and increased chlorophyll a/b ratio, but a decrease in soluble sugars under P. putida treatment with pyrene. This suggests a shift in metabolic priorities towards growth rather than stress mitigation. These findings highlight the complex interactions between plant genotype, microbial strain, and PAH type, underscoring the potential of microbial-assisted phytoremediation. Our study suggests that tailored microbial inoculants, in combination with appropriate plant genotypes, could optimize phytoremediation efforts in PAH-contaminated environments. Future research should focus on soil-based systems and longer-term evaluations to better understand the dynamics of plant-microbe-PAH interactions.